Efektivitas Kebijakan Subsidi Pupuk dan Dampaknya Terhadap Produksi Padi di Kecamatan Pangarenga Kabupaten Sampang - Fajri, Miftahul; Fauziyah, Elys; Hasan, Fuad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the effectiveness of the fertilizer subsidy policy in 2022 and its impact on rice production. The research locations were in three villages, namely Ragung Village, Pacanggaan, Panyirangan, Pangarengan District, Sampang Regency. The number of samples of 30 farmers was taken by the Purposive Sampling Method. The first objective was analyzed using a quantitative descriptive method, while the second objective was with the Cobb Douglass Production Function. The results of the analysis provide an idea that in general, the implementation of fertilizer subsidy policies is in the category of being quite effective. Meanwhile, factors that determine rice production at the research site include: land area, seeds, urea fertilizer, labor and the effectiveness of fertilizer subsidy policies. Improvements that need to be made to increase the effectiveness include: improving the process of preparing the RDKK (Definitive Plan for Group Needs) by increasing the intensity of extension workers in its preparation.